Arctic food and energy security at the crossroads - Unc, Adrian; Abou Najm, Majdi R.; Aspholm, Paul Eric; Bolisetti, Tirupati; Charles, Colleen; Datta, Ranjan; Eggen, Trine; Flem, Belinda; Hailu, Getu; Heimstad, Eldbjørg Sofie; Hurlbert, Margot; Karlsson, Meriam; et al. (Springer Nature, 2025)
Arctic food systems blend Traditional Ecological Knowledge with modern, often energy-intensive influences, triggered by colonization. Food systems’ future depends on alignment of tradition with innovation, facilitation of resilience and a heritage-driven interaction with the global economy – at a pace determined by local communities.